Report on the Research, Teaching and Public Administration of the Economics of Agriculture for India - Planning Commission (Planning Commission, 1954)
The first and foremost thing that needs to be said about the report that follows is that however positive and definitive its pronouncements may seem to be, they must be weighed with the thought in mind that we who have prepared it have been in your country only two months and surely have not had time to acquaint ourselves sufficiently with your economy and way of life, and your research, teaching, and public administration in the economics of agriculture, to make any unqualified recommendations. We have been able in these two months to review the results of considerable past research, study project outlines for some research now being planned, and confer with groups, at Delhi, New Delhi and several other centres of research, teaching and administration but this was far from sufficient for such a task as has been assigned us.
Report on the Research, Teaching and Public Administration